Current provision of general practitioner services in or alongside emergency departments in England. Issue 10 (22nd February 2021) - Brant, Heather; Voss, Sarah; Morton, Katherine; Cooper, Alison; Edwards, Michelle; Price, Delyth; Gaughan, James; Edwards, Adrian; Benger, Jonathan
Abstract : Background: In 2017, general practitioners in or alongside the emergency department (GPED), an approach that employs GPs in or alongside the ED to address increasing ED demand, was advocated by the National Health Service in England and supported by capital funding. However, little is known about the models of GPED that have been implemented. Methods: Data were collected at two time points: September 2017 and December 2019, on the GPED model in use (if any) at 163/177 (92%) type 1 EDs in England. Models were categorised according to a taxonomy as 'inside/integrated', 'inside/parallel', 'outside/onsite' or 'outside/offsite'. Multiple data sources used included: on-line surveys, interviews, case study data and publicly available information. Results: An increase of EDs using GPED was observed from 81% to 95% over the study period. 'Inside/parallel' was the most frequently used model: 30% (44/149) in 2017, rising to 49% (78/159) in 2019. The adoption of 'inside/integrated' models fell from 26% (38/149) to 9% (15/159). Capital funding was received by 87% (142/163) of the EDs sampled. We identified no significant difference between the GPED model adopted and observable characteristics of EDs of annual attendance, 4-hour wait, rurality and deprivation within the population served. Conclusion: The majority of EDs in England have now adopted GPED. The availability of capital funding to finance structural changes so that separate GP services can be provided may explain the rise in parallel models and the decrease in integrated models. Further research is required to understand the relative effectiveness of the various models of GPED identified.